Star wars. Episode V, The Empire strikes back [videorecording (DVD)] - Kershner, Irvin; Lucas, George, 1944-; Hamill, Mark; Ford, Harrison, 1942-; Fisher, Carrie (Star wars trilogy., 2008)
Luke Skywalker and his friends, with the aid of the Jedi master Yoda, repel a new assault by their enemy Darth Vader, but not before Han Solo is captured and forced into frozen hibernation.